BMI and Mortality: The Diabetes-Obesity Paradox Examined in a Large US Cohort - Conway RB; Song J; Figaro MK; Lokanadham JS; Perng W; Crume TL; Blot WJ (Diabetes, Metabolic Syndrome and Obesity)
Rebecca Baqiyyah Conway,1,2 Jooyoun Song,3 M Kathleen Figaro,4 Jyothi Sri Lokanadham,5 Wei Perng,1,5 Tessa Lee Crume,1,5 William J Blot6 1Department of Epidemiology, University of Colorado, Anschutz Medical Campus, Aurora, CO, USA; 2American Academy of Epidemiology, Inc., Tyler, TX, USA; 3Department of Psychiatry, Jooyoun Song’s Psychiatry, Seoul, Republic of Korea; 4Heartland Endocrine Group, Davenport, IA, USA; 5LEAD Center, University of Colorado, Anschutz Medical Campus, Aurora, CO, USA; 6Division of Epidemiology, Vanderbilt University Medical Center, Nashville, TN, USACorrespondence: Rebecca Baqiyyah Conway, University of Colorado, Anschutz Medical Campus, 13001 East 17th Place, Mail Stop B119, Aurora, CO, 80045, USA, Email Rebecca.conway@cuanschutz.eduBackground/Objectives: BMI is a major risk factor for diabetes incidence, but a controversial predictor of mortality among those with diabetes.Subjects/Methods: We conducted a mortality follow-up (2002– 2019) of participants aged 40– 79 with young-onset (diagnosed < age 30, n = 1335), older-onset (diagnosed ≥ 30, n = 15,194), and without (n = 62,295) diabetes at cohort entry. Cox analysis with age as the time scale assessing mortality according to BMI after adjusting for multiple potential confounding factors was used.Results: Mean baseline age and diabetes duration at cohort entry were 50.1 and 29.4 years and 55.3 and 7.7 years among those with young- and older-onset diabetes, respectively. During an average of 12.3 years of follow-up, 47% of the young-onset, 40% of the older-onset diabetes, and 22.6% of those without diabetes at cohort entry died. In multivariable adjusted analyses, compared to a BMI of 18.5-< 25 kg/m2, HRs (95% CIs) were 4.10 (1.65– 10.18), 0.69 (0.54– 0.88), 0.81 (0.63– 1.05), 0.64 (0.48– 0.86) and 0.64 (0.54– 0.77) for BMI categories < 18.5, 25-< 30 30-< 35, 35-< 40, 40+ kg/m2 in those with young-onset diabetes. Corresponding HRs (95% CIs) were 2.02 (1.54– 2.67), 0.74 (0.68– 0.80), 0.74 (0.68– 0.80), 0.83 (0.75– 0.91) and 1.09 (0.99– 1.19) in those with older-onset diabetes, and 1.50 (1.36– 1.67), 0.76 (0.73– 0.79), 0.73 (0.70– 0.77), 0.83 (0.78– 0.89) and 1.03 (0.95– 1.10) in those without diabetes. Results were generally similar in analyses stratified by smoking status, gender, race and among those on insulin therapy.Conclusion: Among this low socioeconomic status population with diabetes, overweight and obesity tend to be inversely associated with mortality. Risk factors for complications of diabetes other than BMI may be more clinically relevant when treating patients with diabetes.Keywords: diabetes, BMI, obesity, obesity paradox